Age-related participation and performance trends of children and adolescents in ultramarathon running - Scheer, V.; Di Gangi, S.; Villiger, E.; Nikolaidis, P. T.; Rosemann, T.; Knechtle, B. (Research in Sports Medicine, 2020)
Participation and performance trends as well as the performance differences among sexes in ultra-endurance running have been well described in the adult population; however, less information on such trends existed in youth ultramarathoners. The aim of the present study was to investigate the age-related participation and performance trends of children and adolescent ultramarathoner runners. Data on runners, younger than 19years of age, competing from 1960 to 2018 in distance-limited ultramarathons of 50 km, 100 km, 50miles and 100miles, were analysed. During this period, the number of ultramarathon participation increased, most notably among boys, most runners originated from Europe, and the 50- and 100-km race distances were the most popular. Overall, male runners were faster than female runners, except in the case of European and Oceanian origin, where girls were faster over the 50-km race. The fastest male runners originated from Africa and the fastest girls from Oceania, and the average running speed has largely decreased for both sexes over calendar years. In summary, this study was the first to report details on participation and performance trends in youth ultramarathoners competing in distance-limited ultramarathons.